Exploring the way sexually explicit material informs sexual beliefs, understanding and practices of young men: A qualitative survey. (November 2020) - Charles, Peter; Meyrick, Jane
Little research has examined how exposure to sexually explicit material may affect beliefs, attitudes and actions of young men. This study explored self-reported effects on young males. A 'snowballed' sample of males aged 18–25 years was recruited within one workplace (11/40 response rate). The qualitative survey data were analysed using thematic analysis. Key themes included increased levels of availability/extreme content of sexually explicit material, seen by young men having negative effects on sexual attitudes/behaviours. Participants reported confusion between real and sexually explicit material which informed expectations of a healthy sex life but may be mediated by potential 'buffers' of family openness or sex education.